Neuromuscular fatigue during a long-duration cycling exercise - Lepers, R.; Maffiuletti, N. A.; Rochette, L.; Brugniaux, J.; Millet, G. Y. (Journal of Applied Physiology, 2002)
The effects of prolonged cycling on neuromuscular parameters were studied in nine endurance-trained subjects during a 5-h exercise sustained at 55% of the maximal aerobic power. Torque during maximal voluntary contraction (MVC) of the quadriceps muscle decreased progressively throughout the exercise (P < 0.01) and was 18% less at the end of exercise compared with the preexercise value. Peak twitch torque, contraction time, and total area of mechanical response decreased significantly (P < 0.05) after the first hour of exercise. In contrast, changes in M-wave characteristics were significant only after the fourth hour of the exercise. Significant reductions (P < 0.05) in electromyographic activity normalized to the M wave occurred after the first hour for the vastus lateralis muscle but only at the end of the exercise for the vastus medialis muscle. Muscle activation level, assessed by the twitch interpolation technique, decreased by 8% (P < 0.05) at the end of the exercise. The results suggest that the time course is such that the contractile properties are significantly altered after the first hour, whereas excitability and central drive are more impaired toward the latter stages of the 5-h cycling exercise.